Theatre Reviews - Georgopoulou, Xenia; Pilla, Eleni; Kizelbach, Urszula; Fabiszak, Jacek (Multicultural Shakespeare: Translation, Appropriation and Performance, 2015)
Romeo and Juliet for Two. Dir. Kostas Gakis, Athina Moustaka, Konstantinos Bibis. 104 Theatre, Athens, Greece. Lady Macbeth. Dir. Marios Mettis. Theatro Thentro, Nicosia, Cyprus Hamlet. Dir. Jan Klata. Gdańsk Shakespeare Theatre, Gdańsk, Poland The Taming of the Shrew [Poskromienie złośnicy]. Dir. Katarzyna Deszcz. Stefan Żeromski Theatre, Kielce, Poland